1960
DOI: 10.1113/jphysiol.1960.sp006569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroxine on the synthesis of cholesterol and fatty acids by cell‐free fractions of rat liver

Abstract: We have shown elsewhere (Fletcher & Myant, 1958) that the synthesis of cholesterol from acetate by rat liver slices is increased if the rat is given injections of thyroxine before the liver is removed. If mevalonic acid, instead of acetate, is used as the precursor of cholesterol, this effect is absent or only just detectable. When the daily dose of thyroxine is 20 ,ug or more, synthesis of fatty acids by the liver slices is depressed. It was suggested that treatment with thyroxine stimulates cholesterol synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

1961
1961
1991
1991

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 8 publications
2
15
1
Order By: Relevance
“…These observations are more detailed than those we have already reported (Fletcher & Myant, 1960), which were based only on the naked-eye appearance of the glycogen pellet obtained by centrifugation.…”
contrasting
confidence: 50%
See 2 more Smart Citations
“…These observations are more detailed than those we have already reported (Fletcher & Myant, 1960), which were based only on the naked-eye appearance of the glycogen pellet obtained by centrifugation.…”
contrasting
confidence: 50%
“…At the end of the incubation cholesterol as digitonide and fatty acids as soaps were isolated from the contents of the flasks and assayed for radio-activity by methods described elsewhere (Fletcher & Myant, 1960). The amounts of lipid synthesized were expressed as micromoles radioactive acetate incorporated into cholesterol or fatty acids per gram of fresh liver.…”
Section: Thyroxine and Lipid Synthesis 543 Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any animal that gained weight as readily as normal animals was discarded. The animals were killed between 12 and 20 days after the operation.…”
Section: Methodsmentioning
confidence: 99%
“…Administration of insulin restored the activity to nearly normal levels within 2 hr. Other hormones that have been implicated in stimulating cholesterol biosynthesis are thyroid hormones (12,13) and norepinephrine (14). Guder et al (13) have shown that hepatic HMG-CoA reductase activity was decreased to less than 50% of normal in hypothyroid rats (produced by 13l1 treatment).…”
mentioning
confidence: 99%